2020
DOI: 10.18632/oncotarget.27492
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-1 in human glioblastoma: implications in tumorigenesis and chemotherapy

Abstract: Glioblastoma is one of the most common malignant brain tumors, with which patients have a mean survival of 24 months. Glypican-1 has been previously shown to be overexpressed in human glioblastoma and to be negatively correlated with patient's survival. This study aimed to investigate how glypican-1 influences the tumoral profile of human glioblastoma using in vitro cell line models. By downregulating the expression of glypican-1 in U-251 MG cells, we observed that the cellular growth and proliferation were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 82 publications
(86 reference statements)
0
16
0
Order By: Relevance
“…The signal detected in the cytoplasm might also be attributed to GAGs linked to other PGs during their intracellular synthesis and traffic [ 52 ]. For example, Listik and collaborators have shown that DS is a GAG that is produced through the epimerization of the glucuronic acid in CS into iduronic acid (IduA) by DS epimerase (DS-epi) 1 and 2 [ 20 ]. They have described the expression of DS-epi1 in MCF7, MDA-MB-231, and SKBR3 cell lines, its involvement in cancer progression and showed that the localization of the enzyme in intracytoplasmic organelles may play a decisive role in the tumor growth [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal detected in the cytoplasm might also be attributed to GAGs linked to other PGs during their intracellular synthesis and traffic [ 52 ]. For example, Listik and collaborators have shown that DS is a GAG that is produced through the epimerization of the glucuronic acid in CS into iduronic acid (IduA) by DS epimerase (DS-epi) 1 and 2 [ 20 ]. They have described the expression of DS-epi1 in MCF7, MDA-MB-231, and SKBR3 cell lines, its involvement in cancer progression and showed that the localization of the enzyme in intracytoplasmic organelles may play a decisive role in the tumor growth [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSPGs and their biosynthetic pathways play a major role in aggressive breast cancer metastasis, thus considering promising targets for antimetastatic-therapies [ 19 ]. PGs play essential physiological and pathological roles during cellular development, proliferation, differentiation, and cancer metastasis [ 20 , 21 ]. The GAG chains are able to interact with molecules such as growth factors which are essential for cell differentiation and maintenance of tissue organization during embryo development but also during tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…GPCs are known to be expressed in several cancers and gained attention as possible biomarkers for various cancer progression. At present, the roles for GPC1 and GPC3 in controlling the proliferation of glioma cells have been reported; the overexpression of GPC1 in U87 glioma cells enhanced FGF-2stimulated proliferation of cells through enhancing FGF-2 signaling [18], whereas knockdown of GPC1 in U251 glioma cells reduced the cellular growth and proliferation [19]; GPC3 drived gliomagenesis and initiated the brain hyperexcitability [43]. In fact, the expression of GPC1 and GPC3 appears to be highly tissue speci c. Of six GPCs, GPC1 is abundantly expressed in brain [44].…”
Section: Discussionmentioning
confidence: 99%
“…GPCs have been suggested to act as biomarkers for tumor progression, such as GPC3 for hepatocellular carcinoma [13,14], GPC1 for pancreatic ductal adenocarcinoma [15], GPC5 and GPC1 for prostate cancer [16,17]. GPC1 is universally overexpressed in human glioma [18,19]. It was reported that overexpression of GPC1 in U87 glioma cells enhanced FGF-2stimulated proliferation of cells through enhancing FGF-2 signaling [18], while knockdown of GPC1 in U251 glioma cells reduced the cellular growth and proliferation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation